Introduction of Music Therapy for Stuporous Patient Attached to a Mechanical Ventilator at Bethany Hospital in Tacloban City, Philippines - Almazan, Joseph Uy; Patosa, Florabelle; Argota, Elnora (International Journal of Advanced Nursing Studies, 2013)
Altered levels of consciousness (ALC) are among the most common problems in general medicine which intensive care unit is included. One of its deepest levels is stupor. Meanwhile, it has shown that the use of music therapy improved levels of consciousness in a patient that has altered levels of consciousness and is ventilated. This study was designed to evaluate the effect of music therapy after a series of listening classic CD songs attached to a built-in CD drive of the mechanical ventilator for stuporous patient using earphones in both ears. Quasi –experimental design was adopted utilizing the both primary data and secondary data.   There were 24 stuporous patients invited to participate as respondents with an age range of 23-92 years old.  Four parameters were evaluated: vital signs of patients when attached to a mechanical ventilator with music therapy; duration of the health status; health status as evidenced by a change in level of consciousness based on doctor’s order and nurses notes. Data were analyzed by SPSS version 19.The researchers found out the use of music therapy (attached to the mechanical ventilator) was effective in improving the level of consciousness; this has been useful in implementation in the Intensive Care Unit.